Dynamic digital human models for ergonomic analysis based on humanoid robotics techniques. (28th January 2015) - Magistris, Giovanni De; Micaelli, Alain; Savin, Jonathan; Gaudez, Clarisse; Marsot, Jacques
Digital human models can be used for biomechanical risk factors assessment of a workstation and work activity design for which there is no physical equipment that can be tested using actual human postures and forces. Yet, using digital human model software packages is usually complex and time–consuming. A challenging aim therefore consists in developing an easy–to–use digital human model capable of computing dynamic, realistic movements and internal characteristics in quasi–real time, based on a simple description of future work tasks, in order to achieve reliable ergonomics assessments of various work task scenarios. We developed such a dynamic digital human model, which is automatically controlled in force and acceleration and inspired by human motor control and based on robotics and physics simulation. In our simulation framework, the digital human model motion was controlled by real–world Newtonian physical and mechanical laws. We also simulated and assessed experimental insert–fitting activities according to the occupational repetitive actions (OCRA) ergonomic index. Simulation led to satisfactory results: experimental and simulated ergonomics evaluations were consistent, and both joint torques and digital human model movements were realistic and coherent with human–like behaviours and performances.